Precursor exhausted CD8+T cells in colorectal cancer tissues associated with patient’s survival and immunotherapy responsiveness - Huang, Hao; Ge, Junwei; Fang, Zhang; Wu, Shaoxian; Jiang, Hongwei; Lang, Yanyan; Chen, Junjun; Xiao, Wenlu; Xu, Bin; Liu, Yingting; Chen, Lujun; Zheng, Xiao; et al. (Frontiers in Immunology, 2024)
Exhausted CD8 + T cells represent a distinct cellular lineage that emerges during both chronic infections and cancers. Recent studies have shown that persistent antigen exposure can drive the differentiation of precursor exhausted CD8 + T cells, termed Tpex cells, which are characterized as TCF-1 + PD-1 + CD8 + T cells. Elevated Tpex cell frequencies in the tumor microenvironment (TME) are associated with improved overall survival (OS) in cancer patients and heightened responsiveness to anti-PD-1 therapy. In our present study, we utilized multi-color immunohistochemistry (mIHC) to determine the localization and clinical implications of tumor-infiltrating Tpex cells within the TME of human colorectal cancer (CRC) tissues. We also conducted a multi-omics integrative analysis using single-cell RNA sequencing (scRNA-seq) data derived from both the murine MC38 tumor model and human CRC tissues. This analysis helped delineate the transcriptional and functional attributes of Tpex cells within the CRC TME. Furthermore, we employed spatial transcriptome sequencing data from CRC patients to investigate the interactions between Tpex cells and other immune cell subsets within the TME. In conclusion, our study not only established a method for Tpex cell detection using mIHC technology but also confirmed that assessing Tpex cells within the CRC TME could be indicative of patients' survival. We further uncovered the transcriptional and functional characteristics of Tpex cells in the TME and ascertained their pivotal role in the efficacy of immunotherapy against CRC.